2017
DOI: 10.5539/jmsr.v6n3p1
|View full text |Cite
|
Sign up to set email alerts
|

Key Factor of Graphene Localization on Electrical Conductive Properties of Graphene Filled Polyethylene/Polypropylene Composites during Melt Blending

Abstract: The effect of surfactant-exfoliated graphene (SEG) on the morphology of SEG-filled polyethylene (PE)/ polypropylene (PP) blends has been investigated by image analysis of transmission electron microscope. The electrical conductivity of SEG-filled PE/PP composites strongly depends on the localization of SEG. From theoretical considerations of a previous paper by one of the authors, it is found that the transfer dynamics as well as the stability of different solid nano-fillers at the blends interface reveals a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…11 Zhu et al also found that the thermal conductivity of polymer blends could be greatly enhanced when GNs are trapped at the interface of the blend, and the blend achieved an extremely low thermal percolation threshold. 5,12 Differently, Ray et al 3 reported that enhanced mechanical and thermal properties of biodegradable polylactide/poly(3-caprolactone) (PLA/PCL) blends could also be achieved by selectively distributing functionalized GNs in the dispersion PCL phase, as the functionalized GNs improve the crystallization property of PCL. Obviously, still there is no consistent cognition regarding the effect of selective distribution of GNs on the performance of the polymer blend.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Zhu et al also found that the thermal conductivity of polymer blends could be greatly enhanced when GNs are trapped at the interface of the blend, and the blend achieved an extremely low thermal percolation threshold. 5,12 Differently, Ray et al 3 reported that enhanced mechanical and thermal properties of biodegradable polylactide/poly(3-caprolactone) (PLA/PCL) blends could also be achieved by selectively distributing functionalized GNs in the dispersion PCL phase, as the functionalized GNs improve the crystallization property of PCL. Obviously, still there is no consistent cognition regarding the effect of selective distribution of GNs on the performance of the polymer blend.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the migration and selective location of layered nanoparticles during the melting process and its effect on microstructure and nal property of the polymer blend are very complicated, dependent on the specic thermodynamic and kinetic conditions such as components, surface property of the nanoparticles, melt-compounding sequences and mixing times of the polymer blend, and shear rates. 4,11,12 Despite the abovementioned attempts, the migration mechanism and effect of selective location of GNs on the property of polymer blends are still insufficient, which need to be supplemented and summarized. Therefore, numerous further specic studies are still needed.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, very few studies have been conducted on the impact of RGO on PE/PP compatibilization and performance enhancement. Tu and coworkers studied how RGO affects PE/PP electrical and mechanical properties, when employing different mixing times and speeds [ 15 ], as well as different orders of mixing [ 16 ]. However, the literature is lacking reports on PE/PP/RGO thermal stability and heat deformation resistance.…”
Section: Introductionmentioning
confidence: 99%